2020
DOI: 10.3390/microorganisms8050642
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Bacterial Communities in a Pilot-Scale Vermireactor Fed with Distilled Grape Marc

Abstract: Vermicomposting has been found as a profitable approach to dispose of and treat large quantities of raw grape marc. However, less information is available with regard to its efficiency for treating distillery winery byproducts, even though distillation has been widely used as a way to economically valorize grape marc. As such, we sought to characterize the compositional and functional changes in bacterial communities during vermicomposting of distilled grape marc by using 16S rRNA high-throughput sequencing. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The clear separation between days 0 and 14 provides further evidence about how quickly vermicomposting modulated the physico-chemical, chemical and biological properties of the Mencía distilled marc within the first two weeks of vermicomposting. This goes hand in hand with the rapid compositional and functional changes reported by Gómez-Brandón et al [14,24] and Kolbe et al [13] on raw and distilled grape marc´s bacterial communities during the first stages of the process on a pilot-scale level. Gómez-Brandón et al [19] also found, on a mesocosm scale, that earthworms' activity (Eisenia andrei) promoted the stabilization of grape marc after only two weeks of vermicomposting.…”
Section: Nutrient Dynamics and Microbial Activity During Vermicompost...mentioning
confidence: 95%
See 1 more Smart Citation
“…The clear separation between days 0 and 14 provides further evidence about how quickly vermicomposting modulated the physico-chemical, chemical and biological properties of the Mencía distilled marc within the first two weeks of vermicomposting. This goes hand in hand with the rapid compositional and functional changes reported by Gómez-Brandón et al [14,24] and Kolbe et al [13] on raw and distilled grape marc´s bacterial communities during the first stages of the process on a pilot-scale level. Gómez-Brandón et al [19] also found, on a mesocosm scale, that earthworms' activity (Eisenia andrei) promoted the stabilization of grape marc after only two weeks of vermicomposting.…”
Section: Nutrient Dynamics and Microbial Activity During Vermicompost...mentioning
confidence: 95%
“…The plausible differences between the raw and distilled marcs' initial composition are expected to distinctly affect the dynamics of the vermicomposting process and in turn, the properties of the final vermicompost. Indeed, Gómez-Brandón et al [24] found that distilled grape marc-derived vermicompost was characterized by a reduced bacterial communities' functional diversity, assessed as a proxy of their metabolic capacity when compared to the respective raw marc [13]. Taken together, this highlights the clear need for more comprehensive studies on distilled grape marc to further evaluate the effectiveness of vermicomposting for the biological stabilization of this winery by-product on a pilot-scale level given the limited evidence to date in comparison with raw marc [23][24][25][26] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that, although bacteria and fungi are the main agents behind biochemical decomposition, earthworms play an essential role in vermicomposting, as evidenced by their ability to accelerate decomposition and significantly modify the physical and microbiological properties of the substrate [114]. Furthermore, Gómez Brandón et al [117] treated distilled grape marc through vermicomposting over 42 days, and the results showed significant changes in the bacterial community, accompanied by a two-fold increase in bacterial richness and diversity, both taxonomically and phylogenetically.…”
Section: Vermicomposting As a Strategy To Valorize Vine And Wine By-p...mentioning
confidence: 99%
“…Saccharimonadaceae was found to be more abundant in colorectal cancer (CRC) model mice when chromium was administered [72]. Saccharimonadaceae is also an intestinal metabolizer and microbial degrader in earthworms [73,74].…”
Section: Plos Onementioning
confidence: 99%